Implementation of Optical OFDM Based System for Optical Networks - B U Rindhe; Jyothi Digge; S K Narayankhedkar (Institute of Advanced Engineering and Science, 2014)
Orthogonal frequency division multiplexing (OFDM), a frequency division multiplexing scheme utilized as a digital multi-carrier modulation technique, implemented using optical ﬁber link for practical applications thereby developing optical OFDM using OptSim simulation. OFDM has many advantages over other modulation techniques such as a high resistance to inter-symbol interference (ISI) and it is robust against fading caused by multipath propagation. Optical ﬁber cable (OFC) as a transmission media is used for distortion less transmission of data at a very higher data speed. OFC cable has a lot of advantages over other media. And OFDM over OFC cable will provide data speeds at a very high speed and with very less losses. In this work optical transmitter and receiver for OFDM based optical network has designed for high speed data transmission over optical ﬁber. While modeling the system we have also used post,,pre and symmetric compensation technique to reconfigure the bandwidth along with add drop multiplexer,tunable filters and optical amplifiers to achieve high performance with minimum distortion and low bit error rate (BER).DOI:http://dx.doi.org/10.11591/ijece.v4i5.5261